The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11481-018-9811-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Schizophrenia Diagnosis by Integration of Genetically Correlated Conditions and Traits

Abstract: Schizophrenia is genetically heterogeneous and comorbid with many conditions. In this study, we explored polygenic scores (PGSs) from genetically related conditions and traits to predict schizophrenia diagnosis using both logistic regression and deep neural network (DNN) models. We used the combined Molecular Genetics of Schizophrenia and Swedish Schizophrenia Case Control Study (MGS+SSCCS) data for training and testing the models, and used the Clinical Antipsychotic Trials for Intervention Effectiveness (CATI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
4
2
Order By: Relevance
“…The AUCs from these studies varied substantially, from 0.54 to 0.95. The AIO results reported here fared better than most the studies reviewed, including our previous study, 18 which used not only the PRSs of schizophrenia but also PRSs from other comorbid traits. These results indicated that genetic data, once transformed into AIOs, could be used effectively to classify the diagnosed patients and unaffected controls.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The AUCs from these studies varied substantially, from 0.54 to 0.95. The AIO results reported here fared better than most the studies reviewed, including our previous study, 18 which used not only the PRSs of schizophrenia but also PRSs from other comorbid traits. These results indicated that genetic data, once transformed into AIOs, could be used effectively to classify the diagnosed patients and unaffected controls.…”
Section: Discussioncontrasting
confidence: 64%
“…In the literature, there were multiple studies that used genetic markers to predict schizophrenia diagnosis, 17 including a study from our group. 18 Most of these studies used an SVM algorithm, and the variables were mostly individual SNVs. Only two studies, one of which was our previous study, used external validation samples.…”
Section: Discussionmentioning
confidence: 99%
“…One publication [3] used both manual and random elements for search, and is counted in both categories. Manual tuning by Chen et al (2019) is implied through reported values which were attempted for hyperparameters, but not explicitly stated [5]. Hyperparameters searched systematically using a given set of values are denoted as grid search.…”
Section: Methods Studies Modelsmentioning
confidence: 99%
“…These results still need to be replicated by other cohorts or similar genetic studies, but they suggest different approaches to discover genetic backgrounds in early-onset psychosis and those in late-onset psychosis. There is a high amount of genetic research related to schizophrenia [ 61 , 62 , 63 ], but the underlying difference between schizophrenic individuals with the typical onset age and those with late-onset schizophrenia means that more investigation is needed in this field. Another approach to find the pathophysiology of late-onset psychosis targets the shared liability between late-onset psychosis and the neurodegenerative disorder accompanying psychotic symptoms.…”
Section: Precision Medicine In Late-onset Psychosismentioning
confidence: 99%